The Effect of Mother Toddler Class Training on Increasing Parents' Knowledge about Child Development at the Binjai Serbangan Health Center, Air Joman District in 2021 - Kamaliah Ainun (Science Midwifery, 2021)
Mothers and children are the group most vulnerable to various health problems that cause death. The Maternal and Child Health Book (KIA Book) is for the purpose of family independence in maintaining health, preventing and overcoming maternal and child health problems, many mothers do not want to bring their toddlers to the toddler mother class this is due to lack of knowledge so researchers are interested in examining the effect Class training for pregnant women on maternal knowledge, the purpose of this study was to determine the effect of class training for mothers under five on parents' knowledge about child development at the Binjai Serbangan Health Center, Air Joman District in 2021. This research is a pre-experimental design research. The population in this study were all mothers who had toddlers aged 1-5 years, at the Binjai Serbangan Health Center, Air Joman District as many as 80 people, sampling was purposive sampling technique. Analysis of the data used Wilcoxon test is used to see the effect between two variables with a 95% confidence degree. The results of the study looked at the knowledge of parents about children's growth and development before the training for mothers under five at the Binjai Serbangan Health Center, Air Joman District in 2021, the majority had less knowledge, namely 10 respondents (50.0%). Parental knowledge about child development after training for mothers under five at the Binjai Serbangan Health Center, Air Joman District in 2021, the majority had sufficient knowledge, namely 11 respondents (55.0%). The conclusion of these results proves that class training for mothers of toddlers can have a positive effect on increasing parents' knowledge about child development. It is recommended that the training for mothers of children under five can be used as an option in increasing the knowledge of mothers of children under five so that it is expected to reduce the morbidity rate of children under five, especially in the work area of the Binjai Serbangan Health Center, Air Joman District. Class training for mothers under five needs to be given regularly by health workers, especially by midwives who are in the work area of the Binjai Serbangan Health Center, Air Joman District. The conclusion of these results proves that class training for mothers of toddlers can have a positive effect on increasing parents' knowledge about child development. It is recommended that the training for mothers of children under five can be used as an option in increasing the knowledge of mothers of children under five so that it is expected to reduce the morbidity rate of children under five, especially in the work area of the Binjai Serbangan Health Center, Air Joman District. Class training for mothers under five needs to be given regularly by health workers, especially by midwives who are in the work area of the Binjai Serbangan Health Center, Air Joman District. The conclusion of these results proves that class training for mothers of toddlers can have a positive effect on increasing parents' knowledge about child development. It is recommended that the training for mothers of children under five can be used as an option in increasing the knowledge of mothers of children under five so that it is expected to reduce the morbidity rate of children under five, especially in the work area of the Binjai Serbangan Health Center, Air Joman District. Class training for mothers under five needs to be given regularly by health workers, especially by midwives who are in the work area of the Binjai Serbangan Health Center, Air Joman District. It is recommended that the training for mothers of children under five can be used as an option in increasing the knowledge of mothers of children under five so that it is expected to reduce the morbidity rate of children under five, especially in the work area of the Binjai Serbangan Health Center, Air Joman District. Class training for mothers under five needs to be given regularly by health workers, especially by midwives who are in the work area of the Binjai Serbangan Health Center, Air Joman District. It is recommended that the training for mothers of children under five can be used as an option in increasing the knowledge of mothers of children under five so that it is expected to reduce the morbidity rate of children under five, especially in the work area of the Binjai Serbangan Health Center, Air Joman District. Class training for mothers under five needs to be given regularly by health workers, especially by midwives who are in the work area of the Binjai Serbangan Health Center, Air Joman District.